2013
DOI: 10.1016/j.anpedi.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

El proteoma del tejido adiposo subcutáneo muestra heterogeneidad anatómica

Abstract: Introducción El tejido adiposo blanco (TAB) subcutáneo (Sc) humano podría variar dependiendo de su localización anatómica, con diferencias en su perfil proteómico. Pacientes y métodos Se obtuvieron aspirados de TAB-Sc de seis mujeres con IMC >25 kg/m2, sometidas a liposucción. Dicho TAB-Sc se obtuvo de seis localizaciones anatómicas: abdominal superior e inferior, muslo, dorsal, flanco y cadera, analizándose su perfil proteómico mediante electroforesis bidimensional. En muslo y abdomen superior se compararon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…All of the 2DE, image processing and analysis, mass spectrometry (MS) and tandem MS (MS-MS) analysis procedures (MALDI-TOF) have been detailed previously for human samples [9-12,15]. Identities obtained after MS and MS-MS analysis were verified using the MS and MS/MS data obtained to search online databases with the software Mascot (http://www.matrixscience.com) [9-12,15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the 2DE, image processing and analysis, mass spectrometry (MS) and tandem MS (MS-MS) analysis procedures (MALDI-TOF) have been detailed previously for human samples [9-12,15]. Identities obtained after MS and MS-MS analysis were verified using the MS and MS/MS data obtained to search online databases with the software Mascot (http://www.matrixscience.com) [9-12,15].…”
Section: Methodsmentioning
confidence: 99%
“…Identities obtained after MS and MS-MS analysis were verified using the MS and MS/MS data obtained to search online databases with the software Mascot (http://www.matrixscience.com) [9-12,15]. …”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional electrophoresis coupled to MALDI TOF was used to identify proteins that are differentially expressed in visceral white adipose tissue between obese/overweight and control groups and to study the role of the identified proteins in adipocyte differentiation [ 26 ]. Obesity is a well-known causative factor for cardiovascular disease; 2-DE coupled to MALDI TOF was used by Moreno et al to study the anatomical heterogeneity in the proteome of human subcutaneous adipose tissue to identify a close relationship between obesity and cardiovascular disease [ 27 ]. Total body adiposity is known to correlate well with the amount of adipose tissue around the myocardium and the coronary arteries, the so-called epicardial adipose tissue.…”
Section: Separation Techniquesmentioning
confidence: 99%
“…Several studies devoted to understanding the physiological differences between visceral and SQ WAT have been performed, but few studies have addressed the molecular and functional differences between SQ WAT fat depots. To determine the proteomic differences in WAT depots, our laboratory conducted two studies, one in humans and the other in mice, using various adipose depots (Table 2 ; Additional file 2 : Table S2) [ 104 , 105 ].…”
Section: Main Textmentioning
confidence: 99%
“…To determine the proteomic differences in WAT depots, our laboratory conducted two studies, one in humans and the other in mice, using various adipose depots (Table 2 ; Additional file 2 : Table S2) [ 104 , 105 ].…”
Section: Main Textmentioning
confidence: 99%